Functional interplay of histone lysine 2-hydroxyisobutyrylation and acetylation in Arabidopsis under dark-induced starvation. Issue 13 (24th June 2021) - Zheng, Lanlan; Li, Chen; Ma, Xueping; Zhou, Hanlin; Liu, Yuan; Wang, Ping; Yang, Huilan; Tamada, Yosuke; Huang, Ji; Wang, Chunfei; Hu, Zhubing; Wang, Xuening; et al.
Abstract: Lysine 2-hydroxyisobutyrylation (Khib) is a novel type of histone acylation whose prevalence and function in plants remain unclear. Here, we identified 41 Khib sites on histones in Arabidopsis thaliana, which did not overlap with frequently modified N-tail lysines (e.g. H3K4, H3K9 and H4K8). Chromatin immunoprecipitation-sequencing (ChIP-seq) assays revealed histone Khib in 35% of protein-coding genes. Most Khib peaks were located in genic regions, and they were highly enriched at the transcription start sites. Histone Khib is highly correlated with acetylation (ac), particularly H3K23ac, which it largely resembles in its genomic and genic distribution. Notably, co-enrichment of histone Khib and H3K23ac correlates with high gene expression levels. Metabolic profiling, transcriptome analyses, and ChIP-qPCR revealed that histone Khib and H3K23ac are co-enriched on genes involved in starch and sucrose metabolism, pentose and glucuronate interconversions, and phenylpropanoid biosynthesis, and help fine-tune plant response to dark-induced starvation. These findings suggest that Khib and H3K23ac may act in concert to promote high levels of gene transcription and regulate cellular metabolism to facilitate plant adaption to stress. Finally, HDA6 and HDA9 are involved in removing histone Khib. Our findings reveal Khib as a conserved yet unique plant histone mark acting with lysine acetylation in transcription-associated epigenomic processes.